2002
DOI: 10.4049/jimmunol.169.4.2054
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Functional Kinin B1 Receptors in Allergic Airway Inflammation

Abstract: B1 receptors are known to be induced during allergic airway inflammation in animal models. However, little is known regarding in vivo B1 receptor expression in humans. We examined B1 receptor mRNA expression in nasal tissue samples from allergic rhinitis and normal subjects. Allergic rhinitis subjects displayed significantly higher expression of B1 receptor mRNA than did the normal subjects, and nasal allergen challenge increased B1 receptor mRNA expression at 8 to 24 h time points in allergic rhinitis subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 40 publications
1
64
0
Order By: Relevance
“…A recent human study lends further support to this concept. Allergic rhinitis subjects, but not normal subjects, were shown to express B 1 receptors in nasal tissue, and allergen challenge further increased nasal expression of B 1 receptor mRNA (Christiansen et al, 2002). Nasal challenge with the B 1 receptor agonist Lys-des-Arg 9 -BK activated the ERK MAPK in nasal samples from subjects with allergic rhinitis but not in normal subjects, suggesting that the B 1 receptor expressed in nasal tissue is functional and may play a role in human airway inflammation.…”
Section: Airway Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A recent human study lends further support to this concept. Allergic rhinitis subjects, but not normal subjects, were shown to express B 1 receptors in nasal tissue, and allergen challenge further increased nasal expression of B 1 receptor mRNA (Christiansen et al, 2002). Nasal challenge with the B 1 receptor agonist Lys-des-Arg 9 -BK activated the ERK MAPK in nasal samples from subjects with allergic rhinitis but not in normal subjects, suggesting that the B 1 receptor expressed in nasal tissue is functional and may play a role in human airway inflammation.…”
Section: Airway Diseasementioning
confidence: 99%
“…The cytokines may be supplied by fixed macrophages, such as those in the reticuloendothelial system, in this form of blood-borne endotoxin stimulation. Clinical samples of chronic inflammatory tissues (nasal tissue samples from subjects with allergic rhinitis, psoriatic skin) show the up-regulation of the B 1 receptor (mRNA in both systems, downstream MAP kinase signaling in nasal samples) without the down-regulation of the preformed B 2 receptor (Schremmer- Danninger et al, 1999;Christiansen et al, 2002). Whether each kinin receptor subtype mediates different aspects of the inflammatory response is an issue of considerable interest.…”
Section: B Inflammationmentioning
confidence: 99%
“…Up-regulation of the bradykinin B 1 receptor has been found in airway and other tissues during inflammation (Christiansen et al, 2002;Hara et al, 2008;Vianna et al, 2003); the hyperresponsiveness to bradykinin or up-regulation of the bradykinin B 2 receptor has been reported in airway inflammation models (Ellis et al, 2004;Kim et al, 2005). Data obtained previously have demonstrated that NF-ÎșB signaling plays an important role in the process up-regulation of the bradykinin B 1 receptor (Moreau et al, 2007;Ni et al, 1998;Sabourin et al, 2002;Schanstra et al, 1998).…”
Section: Discussionmentioning
confidence: 90%
“…B 3 receptors are also expressed in cultured ASM cells, although less is known about their function (10). B 1 receptor expression is inducible, has been shown to be modulated by interleukins, and predominantly mediates the rapid acute response of asthma (smooth muscle contraction or relaxation) (3,4). B 2 receptors are responsible for most of the biological effects of kinins, including arterial vasodilatation, plasma extravasations, vasoconstriction, activation of sensory fibers, and stimulation of the release of prostaglandins, endothelium-dependent relaxing factor (from endothelia), noradrenalin (from nerve terminals and adrenals), and other endogenous agents (16).…”
Section: Discussionmentioning
confidence: 99%